Laparoscopic Sleeve Gastrectomy Feasible for Bariatric Revision Surgery - Berende, Cornelis Adrianus Sebastianus (Springer-Verlag, 2011)
Bariatric revision surgery is associated with several complications that can be attributed to decreased quality of tissue and complexity of the surgery. A laparoscopic sleeve gastrectomy is a simple technique with potential advantages. Therefore, the results of this procedure were evaluated as a revisional option. Fifty-one patients underwent laparoscopic sleeve gastrectomy (LSG). Indications for the LSG were insufficient weight loss (34 patients, group 1) or vomiting (17 patients, group 2) following a laparoscopic adjustable gastric banding (LAGB) or vertical banded gastroplasty (VBG). Patient and procedure characteristics as well as outcome were collected prospectively. From October 2006 to June 2010, 51 patients with a failed prior bariatic procedure (VBG or LAGB) were converted to (L)SG. The conversion rate was zero. The median procedure time was 99 min (range 54–221) and hospital stay was 3 days (range 2–38). There was no mortality after 30 days. Complications included bleeding (six) and leakage of the staple line (seven). Mean follow-up was 13.8 (2–46) months. LSG as revision surgery for insufficient weight loss resulted in extra weight loss of 52.7%, and the overall extra weight loss was 49.3%. When LSG was performed because of vomiting, 82% was able to eat solid food at follow-up. Of the 65 pre-existent co-morbidities, 21 were resolved and 18 improved. LSG as a revision procedure is feasible. An additional weight loss and further resolution of co-morbidity seem achievable, however, at the cost of a high number of complications. Therefore, revision bariatric surgery should be limited to expert tertiary bariatric centers.